Alternative bacteriophage life cycles: the carrier state of Campylobacter jejuni - Siringan, Patcharin; Connerton, Phillippa L.; Cummmings, Nicola J.; Connerton, Ian F. (Royal Society Publishing, 2014)
Members of the genus Campylobacter are frequently responsible for human enteric disease, often through consumption of contaminated poultry products. Bacteriophages are viruses that have the potential to control pathogenic bacteria, but understanding their complex life cycles is key to their successful exploitation. Treatment of Campylobacter jejuni biofilms with bacteriophages led to the discovery that phages had established a relationship with their hosts typical of the carrier state life cycle (CSLC), where bacteria and bacteriophages remain associated in equilibrium. Significant phenotypic changes include improved aerotolerance under nutrient-limited conditions that would confer an advantage to survive in extra-intestinal environments, but a lack in motility eliminated their ability to colonize chickens. Under these circumstances, phages can remain associated with a compatible host and continue to produce free virions to prospect for new hosts. Moreover, we demonstrate that CSLC host bacteria can act as expendable vehicles for the delivery of bacteriophages to new host bacteria within pre-colonized chickens. The CSLC represents an important phase in the ecology of Campylobacter bacteriophage.